2015
DOI: 10.1186/s40001-015-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abdominal drainage systems on postoperative complication rates following liver transplantation

Abstract: BackgroundDepending on the extent of surgery, coagulation status and the number of anastomoses, drains are routinely used during liver transplantation. The aim of this study was to compare different drain types with regard to abdominal complication rates.MethodsAll consecutive full-size orthotopic liver transplantations (LTX) performed over a 7-year period were included in this retrospective analysis. Abdominal drain groups were divided into open-circuit drains and closed-circuit drains. Data are reported as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…When the literature is reviewed, it has been seen that drain use increased the abdominal inflammation and secondary to that, complications occurred. [26,27] As a conclusion of our study, we think that intra-abdominal drain triggered the inflammatory process and negatively affected the recovery of the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 56%
“…When the literature is reviewed, it has been seen that drain use increased the abdominal inflammation and secondary to that, complications occurred. [26,27] As a conclusion of our study, we think that intra-abdominal drain triggered the inflammatory process and negatively affected the recovery of the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 56%
“…This study also showed more infectious complications when drains were used 3 . It was suggested by Weiss and colleagues not to use open‐circuit drains, as these drains were associated with significantly more intra‐abdominal infections 4 . The question remains if the benefits of abdominal drains (i.e., early detection of postoperative complications) outweigh their risks (i.e., intra‐abdominal infections and potential overtreatment of “subclinical” biliary leaks or infections).…”
Section: Discussionmentioning
confidence: 67%
“…Others believe that they are not as useful and only serve to increase potential risk for infection and may even be a reason for increased length of stay post-transplant. [1][2][3][4][5][6] A similar argument and debate is made over the use of T-tubes. It is well known that biliary complications are still a major cause of long-term morbidity after LT. [7][8][9][10] In addition to technical and vascular issues leading to biliary complications, surgeons have debated whether or not using a T-tube is contributing to or reducing the occurrence of these complications.…”
Section: Introductionmentioning
confidence: 98%
“…The current SOC for surgical drain monitoring is manual, and despite the necessity of surgical drains, there is a significant risk of complication and inadequate temporal detection of these events. 5 The drain monitoring process has previously been examined for ways to improve, 4 as studies have underscored how burdensome complications may be. 2 Moreover, increased risk of infection has been attributed to longer length of stay with a surgical drain.…”
Section: Discussionmentioning
confidence: 99%